Non-small-cell lung cancer: how to manage MET exon 14 skipping mutant disease - Juan Bautista Blaquier; Gonzalo Recondo (BioExcel Publishing Ltd, 2022)
Several oncogenic mechanisms have been identified for MET, including MET amplification, fusions, mutations in the tyrosine kinase domain and exon 14 skipping alterations. MET exon 14 mutations are found in about 3-5% of non-small-cell lung cancers. Dysregulation of the MET receptor leads to cell proliferation and survival by activation of the PI3K-AKT-TOR and RAS-RAF-MET-ERK canonical pathways. Targeting the MET tyrosine kinase domain in the setting of MET exon 14 mutations using effective MET tyrosine kinase inhibitors is a current targeted therapy option for patients with metastatic lung cancer. In this Review, we focus on the management of patients with MET exon 14 skipping alterations by addressing the biology of the MET receptor and exon 14 skipping mutations, current treatment strategies, and sequential treatment options based on resistance mechanisms to MET inhibitors in patients with non-small-cell lung cancer.